A Call to Action to Review the USPSTF's Recommendation for Testicular Self-Examination. Issue 5 (October 2022) - Rovito, Michael J.; Allen, Keri; Nangia, Ajay; Craycraft, Mike; Cary, Clint; Lutz, Michael; Lyon, Timothy; Fadich, Ana; Baird, Bryce; Welch, Morgan Garrett; Alcantara, Alexie
We urge the United States Preventive Services Task Force (USPSTF) to call for a formal review of the evidence regarding testicular self-examination (TSE). Twelve years have since passed since the evidence was last formally analyzed where normally re-reviews occur in 5-year cycles. If they would decide to move forward with this action, we ask for the USPSTF to review their methods for establishing recommendations to optimize their rating system operationalization process. Finally, emerging evidence demonstrates a net positive effect of TSE. This stands in contrast to the assertions of TSE's supposed harm that is prevalent in the literature as well as the rationale behind the USPSTF's "D" rating of TSE.